Alternative methods for evaluating financial sustainability of an enterprise - Yeletskykh, S. (Економічний вісник Донбасу, 2017)
The importance of financial stability for maintaining the financial potential and economic growth of the whole national economic system has been substantiated, the indices of company’s financially stable development have been defined, a complex methodological approach to the assessment of company’s financially stable development has been proposed. Обґрунтовано значення фінансової стійкості для забезпечення фінансового потенціалу та економічного зростання усієї господарської системи країни, визначено складові фінансово стійкого розвитку підприємства, запропоновано альтернативні методи щодо оцінювання фінансово стійкого розвитку підприємства. Обосновано значение финансовой устойчивости для обеспечения финансового потенциала и экономического роста всей хозяйственной системы страны, определены составляющие финансово устойчивого развития предприятия, предложены альтернативные методы оценки финансово устойчивого развития предприятия.